2012
DOI: 10.15369/sujms.24.199
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Expression in Colorectal Cancer is Associated with Malignant Clinicopathological Factors

Abstract: : This study aimed to evaluate the frequency, distribution, and corresponding histology of MUC1 expression in colorectal cancer and examine its association with clinicopathological factors. MUC1 expression was con rmed in 86 of 169 surgically resected colorectal cancers 51% , although the ratio of MUC1-positive cells was less than 5% in 33 cases 20% , 5-50% in 46 cases 27% , and greater than 50% in only 7 cases 4% . None or less than 5% of MUC1 expression cases were classi ed as L-group cancers 116 cases, 69% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…4 reported that all small intestinal adenocarcinomas showed a variable degree of CK7 expression diffuse in 54 and focal in 46 ; in contrast, only 4 in this study showed focal expression in secondary colorectal adenocarcinomas. We also confirmed that only 7 4 of 169 colorectal adenocarcinomas exhibited a MUC1 positive cell ratio of 50 , while ratios this high were shown in 41 70 of 59 pancreatic adenocarcinomas and 3 30 of 10 small intestinal adenocarcino-mas 18 . Moreover, genetic abnormalities of colorectal cancer e.g., APC gene mutations do not always apply to small intestinal cancers 5,6,19 .…”
Section: Discussionsupporting
confidence: 78%
“…4 reported that all small intestinal adenocarcinomas showed a variable degree of CK7 expression diffuse in 54 and focal in 46 ; in contrast, only 4 in this study showed focal expression in secondary colorectal adenocarcinomas. We also confirmed that only 7 4 of 169 colorectal adenocarcinomas exhibited a MUC1 positive cell ratio of 50 , while ratios this high were shown in 41 70 of 59 pancreatic adenocarcinomas and 3 30 of 10 small intestinal adenocarcino-mas 18 . Moreover, genetic abnormalities of colorectal cancer e.g., APC gene mutations do not always apply to small intestinal cancers 5,6,19 .…”
Section: Discussionsupporting
confidence: 78%